"Habituat[ing] to Reflection": Hannah More's Romantic Novel. Issue 1 (April 2016) - Isom, Rachael
Abstract : This essay re-examines Hannah More's controversial novel, Cœlebs in Search of a Wife (1809), in light of its formal connections to the occasional meditation, the soliloquy, and the poetic genre M. H. Abrams has termed the Greater Romantic Lyric. The essay argues that More, in attempting to attract both Evangelical and secular readers, creates the prototype for a new novel form. Her protagonist learns and models a reflective practice that, like Romantic lyrics and their devotional predecessors, transforms quotidian subjects matter into objects of structured, meditative soliloquies. By reading Cœlebs as a hybrid text that invokes devotional, dramatic, and lyric traditions, this essay suggests that More's novel disrupts notions of separate male and female, secular and religious Romanticisms. Despite Cœlebs 's near disappearance from the canon of Romantic fiction, More's influence on the novel persists in the borrowing of her reflective trope by female novelists well into the nineteenth century.